Dose-Response Effects of Acute Aerobic Exercise Duration on Cognitive Function in Patients With Breast Cancer: A Randomized Crossover Trial - Salerno, Elizabeth A.; Rowland, Kendrith; Hillman, Charles H.; Trinh, Linda; Kramer, Arthur F.; McAuley, Edward (Frontiers in Psychology, 2020)
Objective To examine the differential effects of acute exercise duration on domains of executive function and processing speed in patients with breast cancer. Methods Participants (N = 48, Mage = 56.02 ± 10.99) completed two sessions in counterbalanced order: moderate-intensity treadmill walking and sitting. Participants were also randomized to one of three duration conditions: 10 (n = 15), 20 (n = 16), or 30 (n = 17) min, reflecting the length of time spent walking and sitting. Immediately before and after each session, women completed a battery of cognitive tasks (e.g., inhibition, cognitive flexibility, spatial working memory, and processing speed). Results Within- and between-subjects repeated-measures analyses of variance revealed time by condition interactions on both processing speed (p = 0.02) and spatial working memory (ps < 0.07), such that women demonstrated improved cognitive functioning regardless of the time spent walking. There were also several moderately sized three-way (e.g., time by condition by duration) interactions driven by declines in cognitive functioning after sitting on cognitive flexibility in the 10 (d = -0.96) and 30-min (d = -0.52) groups and inhibition in the 20-min group (d = 0.75). On the processing speed task, women performed significantly faster after walking compared with after sitting in the 20-min group (d = -0.24). Conclusions For select cognitive domains, walking anywhere from 10 to 30 min is associated with significant benefits. Our findings suggest the need for further research into the mechanisms and dose–response relationships between acute exercise and cognition as well as how such acute bouts may be accumulated for larger, lasting cognitive benefits after breast cancer. Clinical Trial Registration www.ClinicalTrials.gov, identifier NCT04255225